Peer-to-peer application using Microsoft .Net Framework / Tan Boon Yin - Tan, Boon Yin (2004)
Peer-to-peer (P2P) application such as Napster and Gnutella that communicate us peers sharing and receiving information are becoming common place as a means for users connected on large networks to take advantage of the vast resources available to them. The Microsoft .NET Framework provides a rich platform for building P2P applications. The main objective of this thesis is to develop a simple, effective, attractive, interactive, convenient and user friendly instant messaging and file sharing P2P application. This thesis also explains the concepts that make up P2P applications. The P2P application model, discovering others peers, and querying peers for information are discussed. Basically, this P2P application includes three modules server module, client module and library module. Server module handles all the server functionalities like listening to connections and receiving messages. Client module handles all the client functionalities including call request and call initiation. Library module handles all the Windows Fonn Controls and also acts as a middle agent for the communication between client and server. The Microsoft .Net is the software development platform to he used widely through out the project. This project also will emphasize the advantages of Microsoft .Net in developing the P2P application. Microsoft SQI Sen er 2000 or Microsoft SQL Server Desktop engine (MSDE) will he used to manage the database while Windows XP Professional will be my project development platform.